A revised understanding of Tribolium morphogenesis further reconciles short and long germ development. - Matthew A Benton (PLoS Biology)
In Drosophila melanogaster, the germband forms directly on the egg surface and solely consists of embryonic tissue. In contrast, most insect embryos undergo a complicated set of tissue rearrangements to generate a condensed, multilayered germband. The ventral side of the germband is embryonic, while the dorsal side is thought to be an extraembryonic tissue called the amnion. While this tissue organisation has been accepted for decades and has been widely reported in insects, its accuracy has not been directly tested in any species. Using live cell tracking and differential cell labelling in the short germ beetle Tribolium castaneum, I show that most of the cells previously thought to be amnion actually give rise to large parts of the embryo. This process occurs via the dorsal-to-ventral flow of cells and contributes to germband extension (GBE). In addition, I show that true 'amnion' cells in Tribolium originate from a small region of the blastoderm. Together, my findings show that development in the short germ embryos of Tribolium and the long germ embryos of Drosophila is more similar than previously proposed. Dorsal-to-ventral cell flow also occurs in Drosophila during GBE, and I argue that the flow is driven by a conserved set of underlying morphogenetic events in both species. Furthermore, the revised Tribolium fate map that I present is far more similar to that of Drosophila than the classic Tribolium fate map. Lastly, my findings show that there is no qualitative difference between the tissue structure of the cellularised blastoderm and the short/intermediate germ germband. As such, the same tissue patterning mechanisms could function continuously throughout the cellularised blastoderm and germband stages, and easily shift between them over evolutionary time.